2019
DOI: 10.1002/art.40731
|View full text |Cite
|
Sign up to set email alerts
|

Innate Lymphoid Cells and T Cells Contribute to the Interleukin‐17A Signature Detected in the Synovial Fluid of Patients With Juvenile Idiopathic Arthritis

Abstract: Objective Evidence suggests that aberrant function of innate lymphoid cells (ILCs), whose functional and transcriptional profiles overlap with those of Th cell subsets, contributes to immune‐mediated pathologies. To date, analysis of juvenile idiopathic arthritis (JIA) immune pathology has concentrated on the contribution of CD4+ T cells; we have previously identified an expansion of Th17 cells within the synovial fluid (SF) of JIA patients. We undertook this study to extend this analysis to further investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Recent studies have suggested that knee OA might be considered a chronic inflammatory disorder, elevated levels of IL-1, IL-6, IL-17,TNF-α, and other acute-phase proteins that are found in patients with cartilage degradation [25]. A kind of conventional viewpoint is that inflammatory mechanism plays a crucial role in the pathogenesis and evolution of cartilage degeneration and expression of inflammatory reaction [26][27][28]. IL-17 is one of the most important regulators of innate and adaptive immune responses, and it is expressed in synovial tissues, and could contribute to cartilage degeneration and synovial infiltration in joint by inducing the release of chemokines by chondrocytes [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that knee OA might be considered a chronic inflammatory disorder, elevated levels of IL-1, IL-6, IL-17,TNF-α, and other acute-phase proteins that are found in patients with cartilage degradation [25]. A kind of conventional viewpoint is that inflammatory mechanism plays a crucial role in the pathogenesis and evolution of cartilage degeneration and expression of inflammatory reaction [26][27][28]. IL-17 is one of the most important regulators of innate and adaptive immune responses, and it is expressed in synovial tissues, and could contribute to cartilage degeneration and synovial infiltration in joint by inducing the release of chemokines by chondrocytes [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…When patients were divided according to treatment, DN and γδ T cell levels were significantly lower (p = 0.001, p = 0.02, respectively) in patients receiving methotrexate (MTX) than in patients not receiving MTX [71]. However, in another study of JIA, 80% of CD4 -CD8of T cells were γδ T cells and γδ cells secreting IL-17 were positively correlated with innate lymphoid cells (ILC) type 3 secreting IL-17, which in turn correlated with disease severity by physician visual analogue score (VAS) [72]. In another study, when analyzed in relation to subsets of JIA, an elevated percentage of γδ T cells in PB was found in quiescent systemic JIA which decreased in active disease [73].…”
Section: Numerical Evaluation and Relationship To Disease Activitymentioning
confidence: 99%
“…Once it occurs in the joint, inflammatory Th cell activation can occur independent of conventional TCR signaling . Thinking along such lines may also explain recent findings in patients with oligoarticular or polyarticular JIA, in whom an IL‐17 signature in synovial fluid is driven by a whole potpourri of contributors comprising γδ T lymphocytes and receptor‐negative innate lymphoid cells, but also CD4+ and CD8+ lymphocytes .…”
Section: Introductionmentioning
confidence: 95%